Pengenalan Budaya Keselamatan Bagi Pelajar Sekolah Menengah Kejuruan Penerbangan di Lampung dan Sidoarjo - Oke Hendra; Dwi Lestary; Pangsa Rizkina Aswia; Nawang Kalbuana; Martha Saulina (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2022)
The culture of safety in the aviation world is very important, especially for the younger generation. For example, the younger generation is students who are taking aviation education such as Aviation Vocational High School. The purpose of this community service activity is to introduce knowledge about what and how to form a safety culture that needs to be conveyed to the lay community, especially to the younger generation in this case aviation vocational high school students so that they can become pioneers from an early age in applying behaviors that care about things related to safety and also become agents of change that transmit the virus of kindness to the environment in which they lived later. The method used in the activity was a presentation delivered by the resource persons in this case were lecturers and cadets of the Aircraft Accident Relief study program and then continued with questions and answers with participants from students in Lampung and Sidoarjo in collaboration with Karang Taruna Desa Sedati Gede Sidoarjo, East Java who had registered. This activity is carried out online through a video conferencing application. The result obtained from the activities is that participants can open their insights and knowledge about what and how to form a safety culture so that it is hoped that they can bring out personalities that care about safety (safety awareness) and become agents of change who always behave safety and transmit these personalities in their respective environments.